Beyond best management practices: pelagic biogeochemical dynamics in urban stormwater ponds. Issue 6 (1st September 2013) - Williams, Clayton J.; Frost, Paul C.; Xenopoulos, Marguerite A.
Abstract : Urban stormwater ponds are considered to be a best management practice for flood control and the protection of downstream aquatic ecosystems from excess suspended solids and other contaminants. Following this, urban ponds are assumed to operate as unreactive settling basins, whereby their overall effectiveness in water treatment is strictly controlled by physical processes. However, pelagic microbial biogeochemical dynamics could be significant contributors to nutrient and carbon cycling in these small, constructed aquatic systems. In the present study, we examined pelagic biogeochemical dynamics in 26 stormwater ponds located in southern Ontario, Canada, during late summer. Initially, we tested to see if total suspended solids (TSS) concentration, which provides a measure of catchment disturbance, landscape stability, and pond performance, could be used as an indirect predictor of plankton stocks in stormwater ponds. Structural equation modeling (SEM) using TSS as a surrogate for external loading suggested that TSS was an imperfect predictor. TSS masked plankton–nutrient relationships and appeared to reflect autochthonous production moreso than external forces. When TSS was excluded, the SEM model explained a large amount of the variation in dissolved organic matter (DOM) characteristics (55–75%) but a small amount of the variation in plankton stocks (3–38%). Plankton stocks were correlated positively with particulate nutrients and extracellular enzyme activities, suggesting rapid recycling of the fixed nutrient and carbon pool with consequential effects on DOM. DOM characteristics across the ponds were mainly of autochthonous origin. Humic matter from the watershed formed a larger part of the DOM pool only in ponds with low productivity and low dissolved organic carbon concentrations. Our results suggest that in these small, high nutrient systems internal processes might outweigh the impact of the landscape on carbon cycles. Hence, the overall benefit that constructed ponds serve to protect downstream environments must be weighed with the biogeochemical processes that take place within the water body, which could offset pond water quality gains by supporting intense microbial metabolism. Finally, TSS did not provide a useful indication of stormwater pond biogeochemistry and was biased by autochthonous production, which could lead to erroneous TSS‐based management conclusions regarding pond performance.